Computational methods for self-assembly of DNA nanostructures / Ong Hui San - Ong, Hui San (2016)
Deoxyribonucleic acids (DNA), Ribonucleic acids (RNA) and Proteins are the computational devices of life. Compared to conventional machine, natural hardware has data encoded as molecules and requires molecular biology tools to transform these data in order to perform computation. The feasibility of adapting these substrates into conventional silicon machines has been actively studied leading to the emergence of a new computational paradigm, known as molecular computing. One of the most notable researches under this field is DNA self-assembly computing, by which DNAs autonomously come together and formed complex nanostructures. In this study, the concept of Tetris game to facilitate DNA nanostructures fabrication was adapted; whereby different DNA Tetris shapes were used to form complex 2D DNA structures. The efforts are concerted towards self-assembly mechanism of heterogeneous DNA shapes, construction of multiple configurations that can form the identical endstructures, exploration of a less stringent sequence design and predicting connectivity map for the DNA nanostructures assembly. Several approaches have been adopted including development of an autonomous tool that incorporated evolutionary optimization algorithm in constructing these heterogeneous DNA shapes and the application of heuristic through undirected graph theory as an annotation schema to produce the connectivity maps. These approaches have lead to the successful formation of five distinct configurations based on 3 Χ 4 DNA rectangle, which were validated in the laboratory (using Atomic Force Microscopy (AFM) images). This study proved that the fabrication of the DNA nanostructures is no longer limited to sets of specific sequences, but liberated to the conformity of both shapes and sequence combinatorics. This proposed schema has therefore opened up the possibility for competing DNA shapes to self-organize into molecular constructs in an autonomous manner imitating their natural behaviour.